PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 019 DANAU TIGA KECAMATAN RENGAT BARAT - Azman Azman; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is based on the fact that happened in class V SDN 019 Danau Tiga Kecamatan Rengat Barat, which indicates the low quality of mastery of the subject matter IPA. The problem of this research is "Is learning model application cooverative example non-example can improve learning outcomes IPA Student Class V SDN 019 Danau Tiga Kecamatan Rengat Barat?" The purpose of this research is to improve learning outcomes of the IPA on student Class V SDN 019 Danau Tiga Kecamatan Rengat Barat through the implementation of cooverative learning model example of non example. This study took place in the class V SDN 019 Danau Tiga Kecamatan Rengat Barat and held April 12 to April 28, 2016, with the number of subjects as many as 23 people consisting of 10 female students and 13 male students. This research is a classroom action research conducted in two cycles. Based on the results obtained by the percentage of individuals and classical mastery learning model example by applying non example, before the action of 17.4% were completed, the first cycle increased 47.8% and the second cycle an increase of 86.95%. Improved learning outcomes in basic score, 60 increased to 70 in the first cycle by a margin increase of 16.7%. In the second cycle the average student learning outcomes back increased to 79.56 margin improvement that occurred from the first cycle to the second cycle is at 12,01%, so the difference in the increase in the value of student learning outcomes as a whole was 28,71%. Departing from the results of these actions can be summed learning model application cooverative learning example non examples are excellent for learning outcomes IPA class V SDN 019 Danau Tiga Kecamatan Rengat Barat.Keywords: Non Example Example Learning Outcomes IPA